Just think of it as normal subtraction. They both have the same denominators all you need to do is subtract. 11/12-7/12 is 4/12 if you simplify which just means to find the number that both 4 and 12 can go into equally the simplified answer would be 1/3. You just need to divide 4 by both the top and the bottom (numerator and denominator).
Answer:
3d
Step-by-step explanation:
My brainliest please
Answer:
x = 10
Step-by-step explanation:
Solve for x:
2 (x + 2) - 7 + x = 27
2 (x + 2) = 2 x + 4:
2 x + 4 + x - 7 = 27
Grouping like terms, 2 x + x - 7 + 4 = (2 x + x) + (4 - 7):
(2 x + x) + (4 - 7) = 27
2 x + x = 3 x:
3 x + (4 - 7) = 27
4 - 7 = -3:
3 x + -3 = 27
Add 3 to both sides:
3 x + (3 - 3) = 3 + 27
3 - 3 = 0:
3 x = 27 + 3
27 + 3 = 30:
3 x = 30
Divide both sides of 3 x = 30 by 3:
(3 x)/3 = 30/3
3/3 = 1:
x = 30/3
The gcd of 30 and 3 is 3, so 30/3 = (3×10)/(3×1) = 3/3×10 = 10:
Answer: x = 10
Answer:
A) 7 + 4(n - 1)
Step-by-step explanation:
The explicit rule follows the form, Tn = a + (n - 1)*(d), where 'a' is the first term and 'd' is the common difference between the numbers
It says that the first term is 7, so 'a' is 7. It also says that the numbers go up by 4 (adding 4 to the previous number), hence 'd' is 4.
Sub these values into the equation:
Tn = 7 + (n - 1)*(4)
Same as: 7 + 4(n - 1)
Answer:
2(n-9)
Step-by-step explanation:
Hi there!
Let "a number" = n.
"The difference" translates to subtraction, so when the question tells us "the difference of a number and 9", it translates to "n-9".
"Twice" means we'll be doubling something. In this case, we're doubling "n-9":
2(n-9)
I hope this helps!